PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN SISTEM KOMPUTER DI SMK - Rini Novita; Syaiful Zuhri Harahap (Jurnal Informatika, 2020)
The use of computer-based instructional media at Vocational High School (SMKN) 3 Pariaman is still limited to a media presentation using power point. Along with the advancement of information and communication technology (ICT), a lot of software that can be used to create interactive learning media. The results of the preliminary survey of the implementation of learning system computer at SMKN 3 Pariaman  shows  that  there  are  no  teachers who use  interactive  learning  media  with Adobe Director software. ICT facilities and infrastructure such as computers, LCD projectors, and internet at SMKN 3 Pariaman existing one, but have not used optimally. Learning media is one important factor in improving student learning outcomes. The selection of learning media in accordance with the needs  and  characteristics  of  students  can  help  students  understand  the  subject  matter. This research aims to produce an interactive learning media that valid, practical, and effective to help students to master the subject of System Computer.The research method used was R&D (research and development) by using 4D development model (define, design, develop and disseminate). The results showed that interactive learning media is valid based on the assessment of each aspect by the validator. interactive learning media is considered  practical based on observation and responses teacher and student. This shows that, Interactive Learning Media otherwise effective use as a medium of learning in improving student learning outcomes.Keywords: Interactive Learning Media, Sistem Komputer, Adobe Director